Safety health and environment in University Malaysia Pahang - Mohd Pidaus, Mustafa (2008)
The Occupational Safety and Health Act (OSHA) 1994 were introduced in an effort to secure the safety, health and welfare of persons at work against risks to safety or health arising out of the activities of persons. According to OSHA 1994, it is the duty of every employer to ensure, as far as is practicable, the safety, health and welfare at work of all his employees. A study was conducted to investigate the organization of OSHA in UMP to make sure it complied with this act. Some interview with person conduct about the organization was done. And the result showed about organization and table of items organization applied this act with organization. The organization needs some improvement to make sure it complied with act. There are many ways to improve as commitment, employees’ involvement, and OSH training and education is the important keys to the success.